Optimalisasi Peningkatan Sumber Daya Manusia Berbasis Pemberdayaan Masyarakat Di Kampung Wisata Empang - Endang Syarif; Erna Rusmiwati Sukandar (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze strategies for enhancing human resources (HR) through community empowerment activities in the Empang Tourism Village, Indrajaya Village. By leveraging existing tourism potential, these activities are expected to provide relevant training and knowledge to the local community. The research method used is a qualitative approach, with data collection through interviews and observations. The results indicate that community empowerment activities have successfully improved the community's skills in tourism management, local product promotion, and customer service. In addition, these activities have increased awareness of environmental conservation. The study concludes that community empowerment programs can serve as an effective tool for sustainable human resource development in the Empang Tourism Village. It also recommends continuous training and collaboration with various stakeholders to support the sustainability of tourism in the region.